Individual Radiation Sensitivity and Biomarkers: Molecular Radiation Biology - Ainsbury, Elizabeth A.; Abrantes, Ana Margarida; Baatout, Sarah; Baeyens, Ans; Botelho, Maria Filomena; Frey, Benjamin; Foray, Nicolas; Georgakilas, Alexandros G.; Lyng, Fiona M.; Marques, Inês Alexandra; Meade, Aidan D.; Milic, Mirta; et al. (Springer International Publishing, 2023)
In recent years, scientific understanding of the changes radiation makes to the various tissues of the body has vastly increased. Identification of biological markers of radiation exposure and response has become a wide field with an increasing interest across the radiation research community. This chapter introduces the concepts of individual radiosensitivity, radiosusceptibility, and radiodegeneration, which are the key factors to classify radiation responses. Biomarkers are then introduced, and their key characteristics as well as classification are explained, with a particular focus on those biomarkers which have been identified for use in epidemiological studies of radiation risk-as this is a crucial topic of current interest within radiation protection. Brief information on collection of samples is followed by a detailed presentation of predictive assays in use in different settings including clinical applications with responses assessed chiefly in tissue biopsy or blood samples. The sections toward the end of this chapter then discuss the evidence associated with the relationship between age and separately sex, and radiosensitivity, as well as some genetic syndromes associated with radiosensitivity. The final section of this chapter provides a brief summary of how our current knowledge can further support individual, personalized, uses of radiation, particularly in clinical settings.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biomarkers; Genetic syndromes; Personalized treatment; Radiation sensitivity; Radiation therapy; Sex